Implementation of the Anti-Corruption Village Program in Sudagaran Village, Banyumas Subdistrict, Banyumas Regency - Atta Evie Nur Ainy; Indah Ayu Permana Pribadi; Chamid Sutikno; Zaula Rizqi Atika; Ariesta Amanda (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The Anti-Corruption Village Program, initiated by Indonesia’s Corruption Eradication Commission (KPK), seeks to strengthen village governance based on transparency, accountability, participation, and integrity. In 2023, Sudagaran Village, Banyumas Regency, was designated as the first Anti-Corruption Village in the regency and achieved an “Exceptional” rating with a Village Integrity Index of 96.5, making it an important case for examining policy implementation. This study analyzes the implementation of the Anti-Corruption Village Program using George C. Edward III’s policy implementation framework, comprising communication, disposition, bureaucratic structure, and resources. An empirical qualitative design with a descriptive approach was employed. Data were collected through interviews, observations, and document analysis involving eight purposively and snowball-selected informants. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, while credibility was ensured through source and methodological triangulation. The findings reveal that effective communication, strong implementer commitment, a well-defined bureaucratic structure, and adequate organizational resources collectively supported successful policy implementation. These interrelated dimensions institutionalized transparency, accountability, participation, and integrity within routine village governance, enabling Sudagaran Village to sustain its status as a model Anti-Corruption Village.